Estetrol: From Preclinical to Clinical Pharmacology and Advances in the Understanding of the Molecular Mechanism of Action - Céline Gérard; Jean-Michel Foidart (Adis, Springer Healthcare, 2023)
Abstract Estetrol (E4) is the most recently described natural estrogen. It is produced by the human fetal liver during pregnancy and its physiological function remains unclear. E4 is the estrogenic component of a recently approved combined oral contraceptive. It is also in development for use as menopausal hormone therapy. In the context of these developments, the pharmacological activity of E4, alone or in combination with a progestin, has been extensively characterized in preclinical models as well as in clinical studies in women of reproductive age and postmenopausal women. Despite the clinical benefits, the use of oral estrogens for contraception or menopause is also associated with unwanted effects, such as an increased risk of breast cancer and thromboembolic events, due to their impact on non-target tissues. Preclinical and clinical data for E4 point to a tissue-specific activity and a more selective pharmacological profile compared with other estrogens, including a low impact on the liver and hemostasis balance. This review summarizes the characterization of the pharmacological properties of E4 as well as recent advances made in the understanding of the molecular mechanisms of action driving its activity. How the unique mode of action and the different metabolism of E4 might support its favorable benefit-risk ratio is also discussed.